(untitled) (Technical Journal, 2020)
When the excavation of the underground powerhouse of the Sardar Sarovar Project, India was nearly complete, cracks were observed on the upstream and downstream walls of the powerhouse, and the installed instrumentation readings sounded an alert for the instability of the powerhouse cavern that could possibly derail the project, further excavation in the powerhouse cavern was halted. After completing stabilisation measures, the remaining underground excavations by drill and blast method were to be completed. This paper revisits case studies of controlled blasting for the remaining excavations, namely a construction ramp, turbine pits, draft tube tunnels connecting the powerhouse, and the concrete plugs erected at the exit ends of the draft tube tunnels. To ensure overall stability around the excavations, blast vibration was controlled by planning the excavations in proper sequences. The damage outside the planned line of excavations was controlled by adopting modified line drilling/smooth blasting techniques. The details of the sequence of excavations, drilling and blasting parameters, compiled from previous publications, are presented in this paper. This paper also describes the reasons why concrete plugs were erected in the draft tube tunnels, the details of the concrete plugs, the optimised drilling and blasting procedure for safe removal of the plugs, and the method adopted to quantify the damage.